数控成形铣削准双曲面齿轮加工研究 - 赵永军; 邓效忠; 张华 (Jixie chuandong)
Due to the high efficiency and quality of the modern NC technology,some suggestions are discussed during the manufacturing of Formate hypoid gearsin this paper.This consists of（a） the potential possibility of form millinghypoid gear with figure-shaped tool,（b） the mathematical mode of form milling,（c）obtaining the parameters of adjustment and installation based on the special tool,clamp and the vertical machining centers,then generating the NC codes for machining.At last,the numerical simulation and milling experiment are made to establish the foundation of real experiment theoretically.